The effect of plyometric complex training on lower-limb explosive power in adolescents: a systematic review and meta-analysis - Zhang, J.; Wu, X.; Ye, X. (Frontiers in Physiology, 2025)
Objective: In this meta-analysis, we aimed to examine the effects of plyometric complex training (PT) on lower-limb explosive power in adolescents and explore the moderating role of different training variables.